CFD study of coolant for battery thermal management system - Muhamad Zin, Muhammad Shahir (2022)
The use of battery thermal management system (BTMS) is a smart solution o lower the temperature of battries with the use of proper coolant. Batteries with faster charging and discharging rate were often faced with thermal issues that limit its capabilites to perform efficiently. The use of air as coolant in BTMS to improve its cooling performance and reducing the thermal issues were mainly focusing on the structural design optimization that alter the flow of air. The turbulence nature of air later causes the temperature on the battery surface to be fluctuating irregularly. Nanofluid s then proposed as an alternative coolant in this research 10 reduce the temperature fluctuations in the specified Z-type BTMS design using ANSYS Fluent software. Two-dimensional geometry of both the base model and the optimized parallel plate model were solved using the standard k-Ɛ turbulence model equations with enhanced wall treatment option as the viscous model Solver, which require lesser number of iterations needed than SST k-ω to achieve residuals convergence. The accuracy of the model shows considerably large temperature difference on the mesh generated, with 7.4 K and 12.9 K difference on the maximum and minimum temperature of battery compared o the benchmarked result, originating from the conflicted values on the volumetric heat generation (21.6 W instead of 11,8 W) found from published journals, which also contributes to the inaccurate validation of current model. Initial result using sample nanofluid However shows lower maximum temperature on the base model than the parallel plate model, and is selected for consequent simulations. Mixture of singular, oxidized and nitrogenized nanoparticle dispersed in water and ethylene glycol (1G) as the base fluid were then formulated using the general equation of nanofluid with User Defined Function (UDF) codes for temperature-dependent function of the nanofluid material. Characterization of nanofluid is focused first to study the effect of different type of nanofluid on the resultant temperature, with 4% A12O3-water nanofluid (Case 51)displayed the best cooling capabilities despite having Mouromtseff number of 1,08 at Reynolds number of 2300, lower than some other nanofluid described in this study. Further investigation on the parallel plates model using the selected nanofluid later shows increment of maximum temperature by 0.19 K on the surface area of the battery instead, These fluctuations of temperature and heat flus around the area of the parallel plates were found out 1o be affected by the swirling effect of the fluid caused by the flow obstruction. This study may help other researchers by establishing baseline for the cooling performance comparison of coolant using dimensionless numbers. of selected nanofluid, with suggestions on future research using even lower range of Reynolds number.